Biochemical and anaplerotic applications of in vitro models of propionic acidemia and methylmalonic acidemia using patient-derived primary hepatocytes - Collado, M. Sol; Armstrong, Allison J.; Olson, Matthew; Hoang, Stephen A.; Day, Nathan; Summar, Marshall; Chapman, Kimberly A.; Reardon, John; Figler, Robert A.; Wamhoff, Brian R. (Molecular genetics and metabolism, 2020)
Propionic acidemia (PA) and methylmalonic acidemia (MMA) are autosomal recessive disorders of propionyl-CoA (P-CoA) catabolism, which are caused by a deficiency in the enzyme propionyl-CoA carboxylase or the enzyme methylmalonyl-CoA (MM-CoA) mutase, respectively. The functional consequence of PA or MMA is the inability to catabolize P-CoA to MM-CoA or MM-CoA to succinyl-CoA, resulting in the accumulation of P-CoA and other metabolic intermediates, such as propionylcarnitine (C3), 3-hydroxypropionic acid, methylcitric acid (MCA), and methylmalonic acid (only in MMA). P-CoA and its metabolic intermediates, at high concentrations found in PA and MMA, inhibit enzymes in the first steps of the urea cycle as well as enzymes in the tricarboxylic acid (TCA) cycle, causing a reduction in mitochondrial energy production. We previously showed that metabolic defects of PA could be recapitulated using PA patient-derived primary hepatocytes in a novel organotypic system. Here, we sought to investigate whether treatment of normal human primary hepatocytes with propionate would recapitulate some of the biochemical features of PA and MMA in the same platform. We found that high levels of propionate resulted in high levels of intracellular P-CoA in normal hepatocytes. Analysis of TCA cycle intermediates by GC–MS/MS indicated that propionate may inhibit enzymes of the TCA cycle as shown in PA, but is also incorporated in the TCA cycle, which does not occur in PA. To better recapitulate the disease phenotype, we obtained hepatocytes derived from livers of PA and MMA patients. We characterized the PA and MMA donors by measuring key proximal biomarkers, including P-CoA, MM-CoA, as well as clinical biomarkers propionylcarnitine-to-acetylcarnitine ratios (C3/C2), MCA, and methylmalonic acid. Additionally, we used isotopically-labeled amino acids to investigate the contribution of relevant amino acids to production of P-CoA in models of metabolic stability or acute metabolic crisis. As observed clinically, we demonstrated that the isoleucine and valine catabolism pathways are the greatest sources of P-CoA in PA and MMA donor cells and that each donor showed differential sensitivity to isoleucine and valine. We also studied the effects of disodium citrate, an anaplerotic therapy, which resulted in a significant increase in the absolute concentration of TCA cycle intermediates, which is in agreement with the benefit observed clinically. Our human cell-based PA and MMA disease models can inform preclinical drug discovery and development where mouse models of these diseases are inaccurate, particularly in well-described species differences in branched-chain amino acid catabolism.